A five-year retrospective statistical analysis of maxillofacial injuries in patients admitted and treated at two hospitals of Mysore city - Chandra Shekar B; Reddy CVK (Wolters Kluwer Medknow Publications, 2008)
Objectives: This study aims to provide a five-year retrospective statistical analysis of maxillofacial injuries in patients admitted and treated during 1 st January 1998 and 31 st December 2002 in two hospitals of Mysore city; to determine the age and sex distribution, etiology, type of injury, day and time of accident, and the influence of alcohol and other drugs; andto suggest measures to prevent such injuries. Materials and Methods: After obtaining permission from the concerned authorities, a pre-designed questionnaire was used to collect the necessary data from the two hospitals. The data was then computerized and statistical analysis was done using statistical package for the social sciences (SPSS) windows version 10. Results: Road traffic accident (RTA) was the common cause for maxillofacial injuries. Men sustained more injuries compared to women. The injuries were mostly sustained in the age group of 11-40 years, constituting about 78% of all the injuries. Two wheelers were the most commonly involved compared to other vehicle types. Influence of alcohol at the time of injury was found in about 58% of the patients with maxillofacial injuries. The most number of accidents occurred in the weekends. Mandibular fractures were the most common. Conclusion: RTAs are the most common cause for maxillofacial injuries. If RTAs are considered an epidemic of modern times, then prevention is its vaccine.